Language Style Used by the Main Character in Wednesday Series - Ni Kadek Adiari; I Komang Sulatra (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2023)
This study aims to find out types of language style and the factors that influenced the main character in Wednesday series choosing the language style. The data source of this study is Wednesday series. This study used a qualitative method in analyzing the data. This study applied the theory from Joss (1967) in categorizing the type of language style and the theory from Holmes (1993) to find out the factor that influenced the use of language style. This study found that the main character applied four type of language style from 136 data that was found, it was fifty-three data (39%) of casual style, forty-three data (32%) of formal style, twentyfive data (18%) of intimate style, and fifteen data (11%) consultative style. The dominant style used by the main character in Wednesday series was casual style because the main character in the Wednesday series namely ‘Wednesday’ who is stubborn, ignorant, and doesn't care who he is talking to, so he often uses the casual style when talking to people who are older than him. This study found there are four factors that influenced language style selected by the main character in Wednesday series, namely participant, setting, topic and function.